2008
DOI: 10.1007/s00520-008-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of IV monoclonal antibody infusion reaction for the patient, caregiver, and practice: results of a multicenter study

Abstract: IRs following cetuximab and rituximab administration are common and are associated with measurably increased costs of care. The frequency of IRs suggests the importance of identifying clinical guidelines for intervention and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
2
23
0
2
Order By: Relevance
“…Nevertheless, the incidence rate found in this study is consistent with the 7% reported by Schwartzberg et al [4] in their prospective multicenter study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, the incidence rate found in this study is consistent with the 7% reported by Schwartzberg et al [4] in their prospective multicenter study.…”
Section: Discussionsupporting
confidence: 93%
“…The severity of IRs varies from mild itching, flushing, and fever to life-threatening cardiopulmonary events. In a few extreme cases, deaths have resulted from severe IRs [24]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations